Camille et Pauline Borghèse à Turin - Maria Paola Ruffino (Bulletin du Centre de Recherche du Château de Versailles)
In 1808 the governor general of Piedmont for the Empire, Prince Camillo Borghese, moved to Turin with his wife, Pauline Bonaparte. In the residences intended for them, the Palazzo Chiablese and the Palazzina di Caccia di Stupinigi, the governors enjoyed a decor dating from the second half of the eighteenth century, which, in several apartments, had already been renovated in a neoclassical style by the royal designers and architects Leonardo Marini (1737–1806) and Giuseppe Battista Piacenza (1735–1818). The period of the Empire brought no significant renewal in relation to furniture, notably in textile wall hangings and fabrics, in the residences of Turin. However, for Pauline Bonaparte’s rooms in the Palazzo Chiablese the best craftsmen and suppliers of the court were mobilized, such as the cabinetmaker Francesco Bolgié and the merchant Giuseppe Fedele Cerruti, under the guidance of Giuseppe Battista Piacenza. In Stupinigi, the governor used the eastern apartment, formerly belonging to Prince Benedetto Maurizio, Duke of Chablais, where the eighteenth-century wall hangings are still preserved. This study focuses on the style and characteristics of these fabrics and has enabled the identification of the only work known today from the Royal Manufactory of Veneria, active between 1761 and 1765 under the direction of the Avignon merchant Costa, and the persienne created by a Turin-based producer on a design by Leonardo Marini dated 1782, originally intended for the Princess of Piedmont’s bedroom at Moncalieri Castle.